Intrapopulation variation of Calamagrostis arundinacea (L.) Roth revealed by electrophoretically detected ten enzyme systems - Krzakowa, Maria; Celka, Zbigniew (Biodiversity: Research and Conservation, 2007)
One population of Calamagrostis arundinacea (L.) Roth was studied with ten electrophoretically separated, polymorphic (mean Pg = 0.54) enzyme systems: ACO, ADH, DIA, FDH, GDH, GOT, MDH, PGI, PGM, SKDH and PX. Each of 30 plants showed individual differences in respect of 16 loci. The average values of observed and expected heterozygosities were 0.48 and 0.46 respectively. Mean values of Wright’s fixation index (F = -0.045) suggests that population remains in Hardy-Weinberg equilibrium.